2016
DOI: 10.1128/jvi.01292-16
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the RLR/MAVS Signaling Pathway by the L Protein of Mopeia Virus

Abstract: The family Arenaviridae includes several important human pathogens that can cause severe hemorrhagic fever and greatly threaten public health. As a major component of the innate immune system, the RLR/MAVS signaling pathway is involved in recognizing viral components and initiating antiviral activity. It has been reported that arenavirus infection can suppress the innate immune response, and NP and Z proteins of pathogenic arenaviruses can disrupt RLR/MAVS signaling, thus inhibiting production of type I interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
1
10
0
1
Order By: Relevance
“…In agreement with our studies, several studies have recently reported that expression of a viral RdRP can activate the innate immune system in mammalian cells (81)(82)(83)(84). For instance, transient expression of HCV RdRP NS5B resulted in the induction of PRRs specific for dsRNA, including RIG-I and MDA5 that activate the innate immune signaling pathways in mouse and human hepatocytes (85,86).…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our studies, several studies have recently reported that expression of a viral RdRP can activate the innate immune system in mammalian cells (81)(82)(83)(84). For instance, transient expression of HCV RdRP NS5B resulted in the induction of PRRs specific for dsRNA, including RIG-I and MDA5 that activate the innate immune signaling pathways in mouse and human hepatocytes (85,86).…”
Section: Discussionsupporting
confidence: 91%
“…Although the significance of these findings during natural infections remains to be evaluated, these results indicate that positive selection at mammarenavirus L proteins might result from interaction with the host immune system. In line with this view, a recent work also indicated that the L protein of Mopeia virus can activate the RLR/MAVS signaling pathway, possibly via the production of small RNAs ( Zhang et al. 2016 ).…”
Section: Discussionmentioning
confidence: 76%
“…The ability of MOPV NP to bind this factor is not known, and no cellular partners have been identified so far. Finally, it was recently demonstrated that the polymerase of MOPV, but not that of LASV, is able to induce the activation of RIG-I and MDA5, probably through the synthesis of dsRNA (36). Altogether, these additional mechanisms may account for the differences in pathogenicity and immunogenicity between LASV and MOPV, thereby explaining the attenuation of ML29.…”
Section: Discussionmentioning
confidence: 99%